Understanding the Concept of Numeracy for First Grade of Elementary School Students through Bundle of Sticks - Masfufah, Hanem; Wardana, Mahardika Darmawan Kusuma (MIMBAR PGSD Undiksha, 2024)
The low numeracy ability in first grade of elementary school has a significant impact on the understanding of numeracy concepts at the next level of education. This study aims to prove the influence of learning using Bundle of Stick media on students' understanding of numeracy concepts. This objective was determined considering the low understanding of numeracy concepts in elementary school students. This study uses a quantitative experimental method with the True Experimental Design type. Data were collected through observation and multiple-choice assessment test sheets. This study used a sample of 24 students in each class. Data analysis was carried out using the T-test and Paired Sample T-test. The results of the independent sample t-test showed a significance value of 0.00 <0.05, which means that the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. This shows that students' understanding of numeracy concepts will be better if the Bundle of Stick learning media is applied compared to conventional learning. Furthermore, the results of the Paired Sample t-test showed a significance value of 0.00 <0.05, which means that Ha was accepted and H0 was rejected. This shows that the application of Bundle of Stick learning media can improve the understanding of numeracy concepts. Based on these findings, it can be concluded that the innovation of implementing Bundle of Stick media is effective in improving the understanding of numeracy concepts of first grade students. This study has implications for strengthening students' numeracy skills, so that they are more ready to receive material at the next level of education.